Epidemic characteristics and key measures of prevention and control in key places and units under regular COVID-19 prevention and control - a literature analysis - Peng GAO; Meng-yao LI; Qiao-sheng LI; Jia Yawen; Kang Liangyu; Liu Jue; Liu Min (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine weaknesses in epidemic prevention and control in key places and units during regular coronavirus disease 2019 (COVID-19) containment for improving control measures on the epidemic in the future. MethodsTotally 11 studies on COVID-19 epidemic and its control published up to January 20, 2022 were retrieved from China CDC Weekly. The information on key strategies for COVID-19 epidemic control was collected from relevant documents issued by government departments during the epidemic period. ResultsThe places or units with more COVID-19 infections were characterized by frequent gathering of people, high pedestrian flow, and with relatively closed spaces. Most of the index cases were detected among examinees attending medical institutions for compulsory/voluntary/routine screening test and most of the epidemic outbreaks were related to imported cases or imported good with virus contamination. For the key places and units involved in epidemics without local cases, the implemented preventive measures included preparing anti-epidemic materials, keeping ventilation and cleaning of indoor environment, conducting routine disinfection, improving staff management, implementing monitoring on migrant people, and strengthening the publicity of epidemic prevention knowledge; additional measures implemented in the key places and units with local cases were carrying out immediate epidemiological investigations to identify risk areas and performing nucleic acid testing among populations in risk areas. ConclusionIn prevention and control of COVID-19 epidemic, special concern should be paid to medical institutions and places and units correlated with overseas affairs or imported goods. In future, the measures to be strengthened for epidemic containment are the identification of high risk population, the quarantine of imported cargoes, , strict control of nosocomial infection, and epidemic prevention in holidays.